Binge-eating Disorder and Depression - Which causes which? - Marta Lousa Alves Riquito Marques (2020)
Introduction: Binge eating disorder (BED) is the most prevalent eating disorder, and is characterized by the recurrent episodes of binge eating, at least once a week for three months. Depressive disorder, which includes a variety of mental diseases, often co-occur with BED and sometimes they can be correlated. Objective: This review aims to outline available scientific evidence on the relationship between BED and Depression. Other important theoretical knowledge regarding some mediators will also be mentioned. Methods: The research was conducted targeting articles written in English about the relationship between Binge Eating Disorder and Depression, using PubMed as the database. Results: Sometimes BED and depression can have mediators to link each other or factors that influence the behavior. Binge eating is seen as a coping strategy for regulate negative emotions, including depression, which support emotion regulation model. Moreover, executive functions are decreased by depressive symptoms, which also demonstrate that greater levels of depression are associated with more severe binge eating. In young ages, binge eating can cause later depressive symptoms, which turns BED a major influential factor for depression. Last of all, reciprocal association between eating pathology and depressive symptoms can be supported because negative affect are successfully regulate and reduce in the short term by binge eating, which can also cause an increase of depressive symptoms in the later term. Conclusion: Depression is an important predictor of BED, which is supported by emotion regulation model. Moreover, it is important mention the bidirectional relation that can turn into a vicious circle.